(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Lestari DA, Fiqa AP, Abywijaya IK. 2021. Leaf morphological traits of Orophea spp. (Annonaceae): Living collections of Purwodadi Botanic Gardens, East Java, Indonesia. Biodiversitas 22: 3403-3411. Orophea (Annonaceae) have various benefits and play important roles in lowland forest structures. Due to their importance, various Orophea species currently require identification for research and conservation purposes. One of many important variables for such purpose is leaf morphometrical features. This study aimed to investigate leaf morphometrical variations, measure morphometrical similarities, and identify determinant morphometrical traits for species identification in Orophea spp. As many as 23 living plant specimens of Orophea spp. cultivated in Purwodadi Botanic Gardens (belongs to 4 species: Orophea celebica, O. chlorantha, O. enneandra, O. hexandra and an unidentified Orophea sp.) were observed. Twelve measured leaf morphometrical traits in this study were leaf length and width, petiole length, distance from leaf base to the widest part of the leaf, number of secondary veins, apex and base shape, leaf area, length of leaf margin, length to width ratio, leaf roundness and slimness indices. Data were analyzed using multiple one-way ANOVA, Hierarchical Cluster and Principal Component Analyses from within R. The results highlighted that O. hexandra was the most distinguishable species with number of secondary veins, length to width ratio, and leaf slimness as the most distinct characters. The unidentified species of Orophea sp. exhibited morphometrical characters similar to O. chlorantha. No distinct leaf morphometrical traits were able to be identified as determinant characters to each species. Thus, suggesting leaf morphological traits analyses to be used only as a supporting component for plant identification, while still paying attention to the plant’s generative characters.